Spinal shock in paraplegic dogs and neurorehabilitation - Vong, Natalina Isabel Cheang do Rosário (2024)
The spinal shock (SS) phenomenon requires the need of implementing an early intensive neurorehabilitation protocol. This blinded cohort study, performed in Portugal, aims to observe the evolution of SS through the application of the Spinal Shock Scale (SSS) and its implications in the neurorehabilitation of dogs who suffered a spinal cord injury. 249 dogs were evaluated with the SSS, at the time of admission, and for every six hours for three days. All dogs underwent similar neurorehabilitation protocols including land and underwater treadmill training and functional electrical stimulation. Patients admitted under 48h post-injury (71.5%) had higher SSS scored due to early detection of SS signs. Estimated marginal means of SSS showed an exponential decrease in the first 6h, followed by a relative plateau, which was always faster in non-compressive myelopathy patients. The application of the SSS can be beneficial, mainly to adapt neurorehabilitation protocols to each patient’s needs throughout treatment; Resumo: Choque Espinhal em Cães Paraplégicos e Neuroreabilitação O Choque Espinhal (CE) exige a implementação precoce de protocolos de neurorehabilitação intensiva. Este estudo coorte cego, realizado em Portugal, tem como objetivos observar a evolução do CE através da aplicação do Spinal Shock Scale (SSS) e as suas implicações na neurorehabilitação de cães que sofreram lesão medular. Foram avaliados 249 cães com o SSS, à admissão e a cada seis horas durante três dias. Foram todos submetidos a protocolos semelhantes, incluindo treino em passadeira terrestre, aquática e estimulação elétrica funcional. Pacientes admitidos antes das 48h pós-lesão (71.5%) tiveram pontuações mais elevadas na SSS devido à deteção precoce de sinais de CE. As médias marginais estimadas do SSS mostraram uma diminuição exponencial nas primeiras 6h, seguido de um plateau, sendo sempre mais rápido em pacientes com mielopatias não-compressivas. A aplicação do SSS pode ser benéfica para adequar os protocolos de neurorehabilitação às necessidades de cada paciente ao longo do tratamento.